Fostering Global Success Empowering Young Learners in Online Education: Membina Kesuksesan Global dengan Memberdayakan Pelajar Muda dalam Pendidikan Online - Aryanto, Abdillah Valentina; Indrakurniawan, Machful (Indonesian Journal of Innovation Studies, 2024)
This qualitative descriptive study explores the independent characteristics of second-grade students at Betro Elementary School (SDN Betro) within the context of online learning. Through interviews, observations, and documentation, the study investigates the self-reliance of students, the dynamics of parent-student interaction, and the daily habits cultivated by students in response to online education. Findings reveal a notable level of self-reliance among students, manifested in their ability to complete tasks autonomously and adhere to schedules. Positive communication and collaboration between parents and students are observed, fostering a conducive learning environment. The study underscores the importance of nurturing self-reliance in elementary students for successful online learning and provides valuable insights for educators and policymakers aiming to optimize remote education at the elementary level. Highlight: Student Autonomy: Second graders excel independently in navigating online learning environments. Parental Support: Positive parental engagement enhances children's online learning experience. Educational Impact: Fostering self-reliance in elementary students optimizes online education strategies. Keywoard: Elementary Education, Self-Reliance, Online Learning, Parent-Student Interaction, Qualitative Research